Green Courts in India: Strengthening Environmental Governance? - Student Note - Raghav Sharma (Law, Environment and Development Journal, 2008)
The Constitution of India has been the bulwark of Indian environmental governance. Right to clean environment, as an incident of 'right to life', has become enshrined under Article 21 through judicial interpretation. The Indian experience, involving easy access to justice through Public Interest Litigation, demonstrates that 'independent' and 'powerful' superior courts are indispensable for securing environmental justice. However, this ideal turns into a mirage when the superior courts fail to satisfactorily resolve environmental disputes involving scientific and technical questions due to lack of permanent expert panels to assist them. To surmount this practical impediment, the Law Commission of India has mooted the idea of specialised Environmental (Green) Courts in its 186 th Report which will be structurally modeled on similar courts functioning in Australia and New Zealand . While recognising the significance of a specialised judiciary, this paper criticizes the proposal of the Law Commission as a half hearted attempt in this direction. The proposed structure is utterly unimpressive as it purports to withdraw environmental disputes from the jurisdiction of superior courts while entrusting them to weak Environmental Courts which appear vulnerable to substantial executive interference. It fails to subserve the high aim of efficacious dispute resolution as the proposed courts have been weaned of the wide powers which the superior courts were hitherto exercising in environmental matters. Thus, as an alternative, it is proposed that a more pragmatic course will be to create specialist divisions within the existing Indian High Courts to effectively address the practical problems involved in environmental adjudication.